2015
DOI: 10.1681/asn.2014070717
|View full text |Cite
|
Sign up to set email alerts
|

JAK3/STAT6 Stimulates Bone Marrow–Derived Fibroblast Activation in Renal Fibrosis

Abstract: Renal fibrosis is a final common manifestation of CKD resulting in progressive loss of kidney function. Bone marrow-derived fibroblast precursors contribute significantly to the pathogenesis of renal fibrosis. However, the signaling mechanisms underlying the activation of bone marrow-derived fibroblast precursors in the kidney are not fully understood. In this study, we investigated the role of the Janus kinase 3 (JAK3)/ signal transducer and activator of transcription (STAT6) signaling pathway in the activati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

3
125
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 90 publications
(130 citation statements)
references
References 47 publications
3
125
0
Order By: Relevance
“…19 A recent study has revealed that the TGF-b1-Smad3 pathway induces the transition of monocytes to bone marrow-derived fibroblasts in the course of renal fibrosis. 20 Yan et al 17 showed in this study that TGF-b1-induced expression of aSMA, fibronectin, and COLI was not affected by the pretreatment with CP690550 in rat kidney fibroblasts. These results indicate that the effect of CP690550 on the transition of monocytes to bone marrow-derived fibroblasts could be independent of the TGF-b1-Smad3 pathway; however, an experiment using TGF-b1-treated bone marrow-derived monocytes and CP690550 will be required to clarify it.…”
supporting
confidence: 48%
See 4 more Smart Citations
“…19 A recent study has revealed that the TGF-b1-Smad3 pathway induces the transition of monocytes to bone marrow-derived fibroblasts in the course of renal fibrosis. 20 Yan et al 17 showed in this study that TGF-b1-induced expression of aSMA, fibronectin, and COLI was not affected by the pretreatment with CP690550 in rat kidney fibroblasts. These results indicate that the effect of CP690550 on the transition of monocytes to bone marrow-derived fibroblasts could be independent of the TGF-b1-Smad3 pathway; however, an experiment using TGF-b1-treated bone marrow-derived monocytes and CP690550 will be required to clarify it.…”
supporting
confidence: 48%
“…In this issue of JASN, Yan et al 17 clarified the importance of Janus kinase 3 (JAK3) -signal transducer and activator of transcription 6 (STAT6) signaling in the pathogenesis of renal fibrosis through the activation of bone marrow-derived fibroblasts. Yan et al 17 showed that IL-4 or IL-13 stimulated bone marrow-derived monocytes to express aSMA and extracellular matrix, such as COLI and fibronectin, suggesting that bone marrow-derived monocytes could differentiate into bone marrow-derived fibroblasts (COLI 1 ) and myofibroblasts (COLI 1 /aSMA 1 ) in response to Th2 cytokines IL-4 or IL-13.…”
mentioning
confidence: 99%
See 3 more Smart Citations